Die tekskritiek van die Nuwe Testament (2): ’n Oefening in teorie en praktyk - Jacobs, L. D. (Verbum et ecclesia, 1992)
The textual criticism of the New Testament (2): An exercise in theory and practice This concluding article on New Testament textual criticism focuses on the practical application of a workable method for the evaluation of textual variants in the manuscripts of the New Testament. Six variation units displaying a wide variety of textual problems are discussed, viz the ending of Mark’s gospel, the theological/christological problem in John 1:18, the possible conjectural emendation in Acts 16:12, the ortographical variation in Romans 5:1, the doxology at the end of Romans, and the so-called "command to silence" in 1 Corinthians 14:34-35. The next result in each case does not necessarily produce rousing new insights, but it underlines the need for a balanced approach which weighs all the evidence without prejudice before making a decision on the value of a textual variant.